Potential effectiveness of Chinese herbal medicine Yu ping feng san for adult allergic rhinitis: a systematic review and meta-analysis of randomized controlled trials - Qiulan Luo; Claire Shuiqing Zhang; Lihong Yang; Anthony Lin Zhang; Xinfeng Guo; Charlie Changli Xue; Chuanjian Lu (BMC, 2017)
Abstract Background Chinese herbal medicine formula Yu ping feng san (YPFS) is commonly used for allergic rhinitis (AR). Previous review had summarized the effectiveness and safety of YPFS, however without any subgroup analysis performed to provide detailed evidence for guiding clinical practice. YPFS was recommended for the management of AR by Chinese medicine clinical practice guideline, but the treatment duration of YPFS was also not specified. The aim of this study is to evaluate the effectiveness and safety of YPFS in treating adult AR with the most recent evidence, and attempt to specify the duration of utilisation through subgroup meta-analyses. Methods Seven databases were searched from their inceptions to September 2017. Randomized controlled trials (RCTs) evaluating YPFS for adult AR were included. Methodological quality of studies was assessed using the Cochrane risk of bias tool. Meta-analysis and subgroup meta-analyses were conducted for evaluating the effectiveness of YPFS. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach was used for rating the quality of evidence. Results Twenty-two RCTs involving 23 comparisons were included in this review. YPFS was compared to placebo, pharmacotherapy, and used as an add-on treatment compared to pharmacotherapy. Meta-analyses were feasible for the outcomes of four individual nasal symptom scores and "effective rate". Four individual nasal symptom scores decreased after YPFS' combination treatment: itchy nose (MD-0.46, 95% CI[−0.50, −0.42]), sneezing (MD-0.41, 95% CI[−0.47, −0.35]), blocked nose (MD-0.46, 95% CI[−0.54, −0.39]) and runny nose (MD-0.42, 95% CI[−0.58, −0.26]). Based on "effective rate", meta-analysis showed that YPFS did not achieve better effect than pharmacotherapy (RR1.07, 95%CI [0.94, 1.22), but its combination with pharmacotherapy seemed more effective than pharmacotherapy alone (RR1.27, 95%CI [1.19, 1.34]) (low quality). Subgroup analysis suggested that YPFS was not superior to the second-generation antihistamine (RR1.04, 95%CI [0.90, 1.19]) (low quality). Further, YPFS' combination treatment seemed more beneficial when it was used for more than three weeks (RR1.15, 95%CI [1.01, 1.32]). In addition, YPFS was well-tolerated for treating adult AR. Conclusion Chinese herbal medicine formula YPFS seems beneficial for adult AR. This potential benefit need to be further evaluated by more rigorous RCTs.